Chemical composition of volatile aroma metabolites and their glycosylated precursors that can uniquely differentiate individual grape cultivars. (1st December 2015) - Ghaste, Manoj; Narduzzi, Luca; Carlin, Silvia; Vrhovsek, Urska; Shulaev, Vladimir; Mattivi, Fulvio
Highlights: Molecular profiling of volatile aroma metabolites and their precursors in grapes. Ten genotypes were studied from V. vinifera, V. arizonica, V. cinerea and interspecific crosses. Combined use of two orthogonal techniques: GC-MS and LC-HRMS. 66 volatiles were released after hydrolysis and profiled through GC-MS analysis. 15 glycosides were identified through LC-HRMS and correlation with GC-MS data. Abstract: Every grape cultivar has its own unique genetic characteristics, leading to the production of a different secondary metabolite profile. Aroma is one of the most important aspects in terms of the quality of grapes and previous studies have assigned specific aromas to particular grape cultivars. In this study we present the molecular profiling of volatile aroma metabolites and their precursors in ten selected genotypes, including six Vitis vinifera cultivars, two American species (Arizonica Texas, Vitis cinerea ) and two interspecific crosses. Chemical profiling was achieved through combined use of two orthogonal techniques, GC–MS and LC–HRMS, before and after enzymatic hydrolysis. The results show that both free and glycosidically bound aroma precursors behave differently in each different grape cultivar and species. As many as 66 free aroma volatile molecules (originally existing and released after hydrolysis) were profiled through GC–MS analysis, while 15 glycosylated precursors of volatiles were identified through LC–HRMS and correlation with GC–MS data.